Crises and Merchant Networks in the nineteenth century: The Case of German Networks in Lombardy - Poettinger, Monika (The Historical Review/La Revue Historique, 2013)
During the nineteenth century in Continental Europe, merchant networks founded enterprises wherever comparative or absolute advantages related to natural resources or workers’ capabilities, but also changing economic policies, made it profitable. Incessantly comparing the cost-effectiveness of investments, merchant networks enhanced the efficiency of the entire economic system, but also favoured innovation, introducing technological advancements when feasible and potentially remunerative. At the same time, though, economic crises, more and more dependent on manufacturing and less on agricultural cycles, became manifest and an object of theoretical debate. The paper analyzes how merchant networks envisioned economic crises, if at all, and how the economic decision processes of such organizational structures responded to them. It will be ascertained that, more than sectorial imbalances and insufficient demand, the crisis that merchants really feared was the end of credibility and thus of access to credit. Personal failure could dramatically reduce the level of trust, depriving the merchant system of its functioning principle. The chosen framework of analysis describes the actual economic decision process, on which the distribution of production depended, and its relation to economic cycles.